AUTHORITY AND RESPONSIBILITY OF NOTARY IN THE RETENTION OF DOCUMENTS OF PARTIES OTHER THAN NOTARY PROTOCOL IN THE IMPLEMENTATION OF ITS OFFICE - T. Zikri Yutami Hamda; Yanis Rinaldi; Teuku Abdurrahman (JCH (Jurnal Cendekia Hukum), 2021)
Article 1 number 1 Law 2 of 2014 Concerning on Notary Profession (UUJN) reads that the notary has the authority to make an authentic deed, the article is the main principle of notary duty, after the completion of the signatory of the deed, ends the notary duty at the contractual stage. But the reality is that at the post-contractual stage there are notaries that serve the storage of documents of parties other than notary protocols. This custom affects notary independence in the event of legal problems. Research Method is normative legal research using primary and secondary legal materials. The approach used is a statutory approach and an institutional approach to then conducted in-depth analysis. The results showed the storage of documents of parties other than notary protocols posed a legal risk, moral risk and not accepted by the MPD, the storage of such documents contrary to Article 1, Article 16 Verse (1), Article 53 UUJN for placing themselves as recipients of the document storage and services outside UUJN, Article 1868 and 1338 of the Civil Code limiting notaries to act in accordance with UUJN, the storage of such documents at risk of defavoring dignity and violating the notary code of conduct.